Risk factors for scorpion stings in the beni mellal province of morocco - N Charrab; R El Oufir; A Soulaymani; I Semlali; A Mokhtari; R Soulaymani (Journal of Venomous Animals and Toxins including Tropical Diseases, 2009)
Scorpion stings comprise a serious problem throughout the globe, especially in regions where they are more frequent. In Morocco, Beni Mellal is one of the provinces most affected by this burden. This study aimed to trace the epidemiological profile of scorpion stings in Beni Mellal in order to improve patient care and prevent both morbidity and mortality. Our work is a retrospective study of scorpion stings based on medical charts of Beni Mellal. From 2002 to 2007, 8,340 cases were registered in this province with an average incidence of 1.36‰. The stings were more frequent in summer months, particularly July and August, and between 6 p.m. and 6 a.m. (59.8%). The average age of victims was 26.54 ± 18.42 years. Children were affected in 30.3% of the cases. Of all registered cases, 67.3% of the patients received medical aid in less than an hour after the sting. The envenomation rate (Class II and Class III) was 12.4% and the overall case-fatality rate was 0.42% with a mortality rate of 0.005‰. Statistical analysis of the various studied factors revealed a significant connection among the envenomation class, patient age and evolution.